Poverty Alleviation Policy Strategy Through Sustainability Development Goals (SDGs) and Indonesia's Economic Resources - M. Yoga Jusri Pratama; Siti Zubaidah (Dealings Foundation Institute, 2023)
The purpose of this research is to examine and provide guidelines for local governments, communities, academics, and the private sector in planning and implementing poverty alleviation activities that are more effective, efficient, and on target. In addition, the specific objectives of this study are: 1) increasing the rate of regional economic growth through optimizing potential sources of regional income, 2) increasing per capita income, and 3) reducing poverty, unemployment, and socioeconomic inequality of the community. The research was conducted in Palembang City, South Sumatra, Indonesia, in the last 10 years, namely 2017-2022. The research approach uses qualitative descriptive analysis. Data sources include secondary data and Regional Statistics. The results of this study are based on the Sustainability Development Goals (SDGs) indicators, there are four priority scales in poverty alleviation, namely, Health and Infrastructure (Priority I), Education (Priority II), Food Stability (Priority III), and Population and Employment (Priority IV). Therefore, as a solution to poverty alleviation strategies, a budget approach through optimizing the regional economy and regional sources of income as well as community empowerment factors is important. In addition, involvement between elements (government, organizations, communities, universities, and institutions) is expected to continue as an effort to realize poverty alleviation can be overcome optimally.